Perceptions of selected Filipino laypersons on the professional interior design services portrayed in social media - Babst, Crystal Nicole P. (College of Home Economics, University of the Philippines Diliman, 2023)
Social media increases the majority of laypeople's interest in interior design and familiarity with the benefits the industry and its services can provide. However, there are many varying opinions - both positive and negative - and misconceptions about interior design services. This study attempted to determine the perceptions of selected Filipino laypersons on the professional interior design services portrayed on social media platforms. Specifically, the common perceptions of middle-class Filipino laypersons on interior design services, how social media portrays interior design services today, and why middle-class Filipino laypeople feel that way towards the services in interior design as compared to social media portrayal. Mixed-method research that primarily used a qualitative approach but employed a quantitative approach to address a few complementary questions, which included an online survey, was utilized for data gathering. Snowball sampling was used in the selection of the thirty-one middle-class Filipino laypersons for the online survey questionnaire, which collected their perceptions on the professional interior design services portrayed on social media platforms. Through Thematic analysis, data were interpreted according to the emerging themes. Results revealed that social media significantly improved the understanding of interior design services among Filipino laypeople. The results suggest that the social media algorithm was a causal factor in how content on interior design services reached laypeople. The respondents understood that interior design could go beyond aesthetics, styling, and material choice and that it could be affordable and accessible, despite perceptions evolving in both positive and negative ways. Most respondents would hire an interior designer if they had the chance and the means to do so, but the cost is still a significant deciding factor. Considering the limitations of the study, it is recommended that future studies should involve more participants, ideally 100-200 respondents, and conduct interviews to gather more in-depth data.